The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages the hospital when in-patient treatment is recommended. The patient will benefit not only from the general practitioner's opportunity of discussion with his colleagues, but also from his access to the special departments from which he is now isolated. X-ray, Physiotherapy, Social Service, District Nursing, etc. The Health Centre will also provide opportunities for Health education in the form of lectures, films and individual interviews. The war has thrown into high relief many of the social problems and defects of our present system of social services, of which the general public knew little. It has also changed attitudes, modified social relationships, and broken down many of the restrictions and prejudices which hampered progress broken down old precedents and established new ones, and made it necessary to find entirely new solutions to problems. Many war-time developments represent definite gains in social progress and they must be consolidated within the structure of future social services. 1. Mothers and Babies Mr. Brown, then Minister of Health, in his address to women at the Government conference at the Albert Hall in September, 1943, boasted that many thousands of babies had been born in the stately homes of England during the war. There were plenty of defects in the scheme for evacuation 3 15X/2/464/1